Soin des corps et des vécus des personnes amputées : la prothèse comme technologie de soin singulière - Lucie Dalibert; Valentine Gourinat; Paul-Fabien Groud (Anthropologie & Santé)
The amputation of a lower or upper limb and the fitting of amputees with a prosthesis are primarily a matter of medical cure, in view of the health problems that are very often associated with the loss of a limb. However, far from being a technology that ‘’simply’’ aims to cure the body, i.e., functional repair, the prosthesis is part of a vision of care that not only takes into account the singular needs of amputees, their voice, their projects, but also endeavors to include various bio-psycho-social dimensions. In this article, we analyze the multiple care practices that are inherent to prostheses as care technologies, from the hospital environment to the return home and daily life, in the mid- and long-terms.